Sulaimani Seismic Swarm during Spring 1999, NE IRAQ - Aziz, Bakhtar Kader; Lawa, Fadhil Ahmed Ameen; Said, Baker Muhammad (Sulaimani Journal for Pure and Applied Sciences, 2001)
A swarm of earthquakes struck Sulaimani city, or the first time in the known recorded historical seismology of the area during spring 1999_ More than (73) quakes which have magnitudes ranges between (2-4. 7) degree were recorded, as well as handreds of tremors., The epicenters were indicated They are locating NE Sulaimani by distance of about (5-11)km, The approximate depths of the hypocenters show that the swarm had been generated from shallow depths ranging between (2- 11) km The total energy released was calculated to be about (26 X 1017) erg, which is equivalent to an earthquake of magnitude (5.1) degree. The cause of the swarm interpreted to be the continuous movement of sitak Sulaimani transverse fault during this period.